Clinical characteristics, antihypertensive medication use and blood pressure control among patients with treatment-resistant hypertension: the Survey of PatIents with treatment ResIstant hyperTension study. Issue 11 (November 2019) - Carcel, Cheryl; Neal, Bruce; Oparil, Suzanne; Rogers, Kris; Narkiewicz, Krzysztof; Wang, Ji Guang; Schiffrin, Ernesto L.; Poulter, Neil; Azizi, Michel; Chalmers, John
Abstract : Objective: We evaluated the characteristics of patients with treatment-resistant hypertension (TRH) and the prevalence of TRH in a large multicountry sample of specialist tertiary centres. Methods: The Survey of PatIents with treatment ResIstant hyperTension (SPIRIT) study was a retrospective review of medical records of patients seen at tertiary centres located in Western Europe, Eastern Europe, North America, South America, Australia and Asia. Data on demographics, medical history and medication use were extracted from medical records. Prevalence and incidence of TRH were based upon estimated catchment populations. Results: On thousand, five hundred and fifty-five patients from 76 centres were included, mostly from centres that specialize in hypertension (55%), cardiology (11%) or nephrology (19%). Mean age was 64, 60% were men, 62% were Caucasian, 36% had chronic kidney disease, 41% had diabetes, 12% were smokers and 31% had a previous cardiovascular event. Daytime and night-time ambulatory blood pressure (BP) was the most frequently used measurement for diagnosis (82%). Ninety-five percent of patients were prescribed diuretics, 93% an inhibitor of the renin–angiotensin system, 86% a calcium channel blocker, 74% a beta-blocker and 36% an aldosterone antagonist. The overall estimated mean incidence of TRH was 5.8 per 100 000 per year (ranging between 2.3 and 14.0 across regions) and the corresponding estimated mean prevalence of TRH was 23.9 per 100 000 (ranging between 7.6 and 90.5 across regions). Conclusion: Observed variation likely reflects real differences in patient characteristics and physician management practices across regions and specialities but may also reflect differences in patient selection and errors in estimation of catchment population across participating centres. Abstract : Supplemental Digital Content is available in the text